2019
DOI: 10.1080/23802359.2019.1613178
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome sequence and SNPs of the Korean smeltHypomesus nipponensis(Osmeriformes, Osmeridae)

Abstract: In this study, the mitogenomes of four smelts (Hypomesus nipponensis) were sequenced and the genomic variation and phylogeny were examined. The mitogenome consisted of 16,782 bp and showed 99.5 99.7% sequence similarity with the previously released sequence. A total of 130 single nucleotide polymorphisms were detected and they were present in 2 rRNA genes, 6 tRNA genes, 12 proteincoding genes, and 1 non-coding region. This study provides important information for the classification of H. nipponensis and relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…One non-native fish of interest in the estuary is the Wakasagi, also commonly referred to as the Japanese Pond Smelt (Hypomesus nipponensis, hereon "Wakasagi"). Wakasagi are widely distributed from the Kuril Islands of Russia and coastal regions and lakes of Japan to the South Korean Peninsula (Katayama et al 2001;Ilves and Taylor 2008;Choi and Kim 2019). In Japan, Wakasagi support a commercial freshwater fishery supported by an aquaculture program with annual hatchery releases of >10 billion eggs and newly hatched larvae into lakes and reservoirs (Nakamura and Watanabe 2001).…”
Section: Introductionmentioning
confidence: 99%
“…One non-native fish of interest in the estuary is the Wakasagi, also commonly referred to as the Japanese Pond Smelt (Hypomesus nipponensis, hereon "Wakasagi"). Wakasagi are widely distributed from the Kuril Islands of Russia and coastal regions and lakes of Japan to the South Korean Peninsula (Katayama et al 2001;Ilves and Taylor 2008;Choi and Kim 2019). In Japan, Wakasagi support a commercial freshwater fishery supported by an aquaculture program with annual hatchery releases of >10 billion eggs and newly hatched larvae into lakes and reservoirs (Nakamura and Watanabe 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Smelt is an anadromous species ( Saruwatari et al 1997 ), but now it is cultivated in many reservoirs in South Korea. In a previous study, smelt samples from South Korea were identified as H. nipponensis ( Choi and Kim 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Smelt is an anadromous species (Saruwatari, Lopez, & Pietsch, 1997), however, now it is cultivated in many reservoirs in South Korea. In a previous study, smelt samples from South Korea were identified as H. nipponensis (Choi & Kim, 2019).…”
Section: Introductionmentioning
confidence: 99%